Diabetes, gender and deterioration in estimated glomerular filtration rate in patients with chronic heart failure: Ten-year prospective cohort study. (February 2021) - Kearney, Jessica; Drozd, Michael; Walker, Andrew MN; Slater, Thomas A; Straw, Sam; Gierula, John; Paton, Maria; Lowry, Judith; Cole, Charlotte; Witte, Klaus K; Cubbon, Richard M; Kearney, Mark T
Introduction: We aimed to evaluate the relationship between temporal changes in renal function and long-term mortality in patients with heart failure with reduced ejection fraction (HFrEF) and identify correlates of deteriorating renal function. Methods: A total of 381 patients with HFrEF enrolled in a prospective cohort study between 2006–2014 had eGFR measured at initial visit and at 1 year. Baseline characteristics were used in a multivariate analysis to establish variables that predict deterioration in eGFR. Follow-up data were used to assess whether declining eGFR was related to outcomes. Results: Patients were grouped into tertiles based on percentage change in eGFR. In a multivariate logistic regression analysis, male sex was associated with a 1.77-fold ([95% CI 1.01–2.89]; p = 0.045) and diabetes a 1.66-fold ([95% CI 1.02–2.70]; p = 0.041) greater risk of a decline in eGFR compared to those with stable/improving eGFR. Declining eGFR was associated with a 1.4-fold greater risk of death over 10 years ([95% CI 1.08–1.86]; p = 0.01) and a 3.12-fold ([1.44–6.75]; p = 0.004) greater risk of death at 1 year from second eGFR measurement. Conclusions: In patients with HFrEF diabetes and male sex are independent predictors of a decline in eGFR at 1 year. A decline eGFR over 1 year is associated with higher long-term all-cause mortality.